THE HEATH DATA HUB’S CHOICE TO USE MICROSOFT: BETWEEN RISKS AND PRECAUTIONS WITH REGARD TO HEALTH DATA - BÉVIÈRE-BOYER, Bénédicte (MEDECINE LEGALE DROIT MEDICAL, 2025)
Even though the new French health data platform, also known as Heath Data Hub, is in turmoil because it has been criticized for choosing Microsoft, particularly in light of the Schrems ruling of the European Court of Justice on July 16, 2020, it remains supported by the Council of State in its ruling of October 13, 2020. The study of this case provides a better understanding of the risks, as well as the precautions to be taken for the management of health data at the national and community levels.